Iontophoresis Improves the Impact on the Quality of Life of Children with Primary Hyperhidrosis-A Prospective Study and a Short Review - Florentina Nastase; Camelia Busila; Alin Codrut Nicolescu; Cristina Mihaela Marin; Alin Laurentiu Tatu (MDPI AG, 2024)
Background: Primary hyperhidrosis (PH) is a somatic and idiopathic pediatric skin disease. The eccrine glands are tiny and very numerous, with approximately 3 million distributed throughout the skin. There is no commonly accepted amount of sweating to define hyperhidrosis, but people with this disease suffer real limitations integrating into society, which can be quantified through quality of life measurement scales. We want to draw attention to this disease and its impact on children's quality of life because it is significant and there are no studies conducted on groups consisting solely of children. Methods: There are various quality of life evaluation questionnaires for hyperhidrosis. We studied 103 children with hyperhidrosis by monitoring their sweat severity and its impact on quality of life, using the Hyperhidrosis Disease Severity Scale. We compared the scale results before and after 10 days of iontophoresis. This study includes only children under 18 years old, treated with iontophoresis. Results: The average age of the group is 11.84 ± 2.89 years. Treatment success is recorded in 68 (66.02%) children, but a change in the score is recorded in 74 (71.84%) children. The average HDSS score at T0 is 2.95 ± 0.70, compared to the HDSS score at T1 of 1.92 ± 0.86. Conclusions: Hyperhidrosis has a negative impact on daily life, especially self-esteem, occupational productivity, emotional well-being, and interpersonal relationships. Iontophoresis is a safe and effective treatment method that reduces the severity of hyperhidrosis and increases the quality of life.